Service Robots - Antonio J. R. Neves (IntechOpen, 2018)
The idea of using robots in our daily lives was an inspiring research in the field of robotics during the last decades. Service robots can be found nowadays in warehouses, hospitals, retail stores, city streets, and industrial parks or as personal assistants. The effort on the development of these robots is confirmed by the amount of money invested in projects and companies, the creation on new start-ups worldwide, and, not less important, the quantity and quality of the manuscripts published in journals and conferences worldwide. This book is an outcome of research done by several researchers who have highly contributed to the field of service robots. The main goal of this book is to present the recent advances in the field of service robots.
English
Keywords: Physical Sciences; Engineering and Technology; Automation; Robotics; Service Robot